Understanding the assistance dynamic of the psychiatric emergency service using the fourth generation assessment - Buriola, Aline Aparecida (2017)
A study to comprehend the requests, concerns, and questions of professionals about the assistance dynamic of a psychiatric emergency service. We conducted a case study, using the Fourth Generation assessment method, with 15 participants. We collected data using documental analysis, semi-structured interview and observation and, we used the constant comparative method for analysis. Therefore, two thematic axes arose: a) Comprehending the assistance dynamic of the Psychiatric emergency service and, b) The disarticulation of the psychosocial attention network as a barrier to satisfaction with the assistance in the psychiatric emergency. We considered that the assistance dynamic in the Psychiatric Emergency extrapolated the simple, unique character of stabilizing patients with acute mental disorders, once it directs the user’s flow to the adequate treatment in the psychosocial attention network.